Burkholderia cenocepacia BC2L-C Is a Super Lectin with Dual Specificity and Proinflammatory Activity - Šulák, Ondřej (Public Library of Science, 2011)
Lectins and adhesins are involved in bacterial adhesion to host tissues and mucus during early steps of infection. We report the characterization of BC2L-C, a soluble lectin from the opportunistic pathogen Burkholderia cenocepacia, which has two distinct domains with unique specificities and biological activities. The N-terminal domain is a novel TNF-α-like fucose-binding lectin, while the C-terminal part is similar to a superfamily of calcium-dependent bacterial lectins. The C-terminal domain displays specificity for mannose and l-glycero-d-manno-heptose. BC2L-C is therefore a superlectin that binds independently to mannose/heptose glycoconjugates and fucosylated human histo-blood group epitopes. The apo form of the C-terminal domain crystallized as a dimer, and calcium and mannose could be docked in the binding site. The whole lectin is hexameric and the overall structure, determined by electron microscopy and small angle X-ray scattering, reveals a flexible arrangement of three mannose/heptose-specific dimers flanked by two fucose-specific TNF-α-like trimers. We propose that BC2L-C binds to the bacterial surface in a mannose/heptose-dependent manner via the C-terminal domain. The TNF-α-like domain triggers IL-8 production in cultured airway epithelial cells in a carbohydrate-independent manner, and is therefore proposed to play a role in the dysregulated proinflammatory response observed in B. cenocepacia lung infections. The unique architecture of this newly recognized superlectin correlates with multiple functions including bacterial cell cross-linking, adhesion to human epithelia, and stimulation of inflammation.